2010
DOI: 10.1038/gt.2010.145
|View full text |Cite
|
Sign up to set email alerts
|

Indolactam V/GLP-1-mediated differentiation of human iPS cells into glucose-responsive insulin-secreting progeny

Abstract: Nuclear reprogramming of somatic tissue enables derivation of induced pluripotent stem (iPS) cells from an autologous, non-embryonic origin. The purpose of the current study was to establish efficient protocols for lineage-specification of human iPS cells into functional glucose-responsive, insulin-producing progeny. We generated human iPS cells, which were then guided with recombinant growth factors that mimic the essential signaling for pancreatic development. Reprogrammed with four stemness factors, human f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 49 publications
2
99
1
1
Order By: Relevance
“…It is thought that this response serves to protect the remaining betacells (reviewed in [109]). Indeed, the addition of GLP-1 to stem cell cultures has been reported to improve beta-cell development from human iPS cell-derived PDX1-positive precursors in vitro to the extent that some glucose responsiveness is generated [110].…”
Section: Generation Of Hormone-positive Cellsmentioning
confidence: 99%
“…It is thought that this response serves to protect the remaining betacells (reviewed in [109]). Indeed, the addition of GLP-1 to stem cell cultures has been reported to improve beta-cell development from human iPS cell-derived PDX1-positive precursors in vitro to the extent that some glucose responsiveness is generated [110].…”
Section: Generation Of Hormone-positive Cellsmentioning
confidence: 99%
“…Diabetes-Reprogramming pluripotent cells to pancreatic ␤-like cells from a variety of animal species and humans is a critical step in creating an alternative source of insulin-producing cells (41)(42)(43). Different stepwise protocols that mimic the process of pancreatic development have been used for reprogramming, but the efficiency of the process is still very low, even using pancreatic ␤-cells as iPSC precursors (44).…”
Section: Testing Ipscs In Animal Disease Modelsmentioning
confidence: 99%
“…Two other signaling pathways, NOTCH and HEDGEHOG, have been shown to be involved in the DE differentiation into pancreatic endocrine cells [16] (Figure 1). The inhibition of HEDGEHOG-signaling by Cyclopamine or KAAD cyclopamine induces the generation of PDX1-expressing cells [17,18,25,27,29] , whereas Fibroblast growth factor 10 activates NOTCH signaling, which is involved in the proliferation of PDX1-expressing pancreatic progenitors.…”
Section: Differentiation Into Pancreatic Progenitors and Endocrine Cellsmentioning
confidence: 99%
“…In contrast to PDX1, NGN3 expression is stimulated by a reduction in NOTCH signaling. It has been previously shown that the blockage of NOTCH signaling at this stage may be driven by DAPT (the gamma secretase inhibitor) treatment and thus drive NGN3-expressing cells formation [17,18,27] . Interestingly, these cells have been found to be differentiated from PDX1-expressing pancreatic progenitors after specific treatments.…”
Section: Differentiation Into Pancreatic Progenitors and Endocrine Cellsmentioning
confidence: 99%
See 1 more Smart Citation